Eggs Hatching of Betta Fish (Betta splendens) with The Addition of Ketapang Leaves (Terminalia cattapa Linn) at UPR Mitra Mina Sejahtera Indralaya, Ogan Ilir District - Azhari, Muhammad; Syaifudin, Mochamad; Yonarta, Danang (Politeknik Kelautan dan Perikanan Karawang, 2023)
The limited number of fish seeds is still an obstacle in betta fish cultivation activities due to the low percentage of hatching and high mortality of larvae. This research aims to increase the percentage of egg hatching and survival of betta fish by stimulating ketapang leaves. This research was carried out in a controlled area at UPR Mitra Mina Sejahtera located in Griya Sejahtera Indralaya Housing, Ogan Ilir Regency from June to July 2022. The addition of ketapang leaves as much as 2 g per L (P2) can increase the hatching percentage at 96.97% and betta fish larval survival rate to 87.92%. The water quality obtained from this research is the temperature of P1 ranges from 26.4-27.3°C, P2 ranges from 26.7-27.2, control ranges from 26.5-27.1°C, pH P1 ranges from 6.5-6.9, P2 ranges from 6.5-6.7 and control ranges from 6.9-7.2 and dissolved oxygen P1 ranges from 1.03-1.09 mg per L, P2 ranges from 1.00-1.05 mg per L and control ranged from 1.04-1.10 mg per L.